Development of dietary fiber enriched chicken nugget using rice bran - Haque, ME; Mollah, MBR; Habib, M; Hashem, MA; Azad, MAK; Ali, MS (Meat Research, 2024)
The experiment was conducted to investigate the impact of varying levels of rice bran on the sensory attributes and storage qualities of broiler meat nuggets. Three distinct groups were formed for this purpose: T1 (chicken nuggets without rice bran), T2 (chicken nuggets with 5% rice bran), and T3 (chicken nuggets with 10% rice bran). The analysis encompassed parameters assessed at 0, 14, and 28 days, with sensory evaluation conducted on the first day. The proximate composition of the nugget was examined, revealing significant differences in dry matter (DM), crude protein (CP), Ash and crude fiber (CF) percentages (p<0.05). T3 exhibited notably higher DM, ash and CF content, while T1 showed higher CP. No significant disparities were observed in EE across the treatments. Storage duration significantly influenced DM, CP, ash, and EE content, with an increase noted in DM and CP over time, while ash content decreased. Surface color (CIE L*, a*, b*) measurements of the nugget samples indicated significantly higher lightness in T1 and lower lightness in T3 , with storage duration also impacting lightness, which decreased with time. Treatment had no effect on pH, but storage duration influenced it, with significantly lower pH observed after 14 days of storage. Biochemical analysis revealed that treatment did not affect free fatty acid value (FFA), peroxide value (POV), or Thiobarbituric acid reactive substances (TBARS), although storage duration influenced POV and TBARS values, which increased over time. During sensory analysis, including overall acceptability, no discernible differences were found among the treatments, suggesting that rice bran incorporation up to 10% in nugget preparation does not compromise consumer acceptance.